An Uncommon Presentation of Leptomeningeal Metastases in Breast Carcinoma Detected by F-18 FDG PET/CT - Surya, Gavini; Ajit, Nimmagadda; Priya, Rallapeta Ramya; Hemalatha, Dhamarcherla S.; Devi, Bodagala Vijayalakshmi; Kalawat, Tekchand (World Journal of Nuclear Medicine, 2022)
Leptomeningeal carcinomatosis is a manifestation in which tumor cells migrate into meninges. Breast carcinoma presenting with leptomeningeal metastases is a rare phenomenon that can occur in an isolated form as well as with coexistent parenchymal brain metastases. The gold standard for diagnosis is cerebrospinal fluid analysis, while contrast-enhanced magnetic resonance imaging is the most commonly used imaging modality. Nuclear medicine imaging with flourine-18-fluorodeoxyglucose positron emission tomography/computed tomography has proved to be useful in detecting leptomeningeal metastases and, at times, even before anatomical changes occur. Here, we present a case of breast carcinoma presenting with both pachymeningeal and leptomeningeal metastases 10 years after treatment.
Keywords: breast cancer; F-18 FDG PET/CT; leptomeningeal metastases